Calcium and silicon nanofertilizers improved morphological attributes and fatty acid composition in olive; an insight to synergistic interaction between these elements - Javad Erfani-Moghadam; Abdolkarim Zarei (BMC Plant Biology)
Abstract Background Proper plant nutrition represents a critical determinant influencing the optimal growth, development, yield, and overall quality of fruit in fruit tree cultivation. Calcium (Ca) and Silicon (Si) play pivotal roles in enhancing plant health by reinforcing structural integrity, increasing resilience to environmental stressors and pest infestations, promoting vegetative growth, and regulating the biosynthesis of beneficial plant compounds. The utilization of nano-fertilizers for targeted and controlled nutrient release represents a promising strategy to advance sustainable agricultural practices while minimizing environmental impact. Method The effects of foliar application of Ca and Si nanoparticles were investigated on the morphological attributes and fatty acid composition of olive tree cultivar ‘Zard’. A factorial experiment was conducted in the form of a completely randomized block design with three replications. Three concentrations of chelated Ca (7%) nanoparticles (0, 400, and 800 mg L−1) and Si oxide (2%) nanoparticles (0, 30, and 60 mg L−1) were foliar sprayed on olive trees grown under field conditions. Foliar applications were administered twice during the growing season: initially in mid-May following fruit set, and subsequently in July. The physical characteristics of fruits and leaves, along with their Si and Ca concentrations, were determined by analyzing 50 samples per treatment, with results expressed as mean values. The fatty acid composition of olive oil was analyzed by gas chromatography (GC). The data sets were subjected to the normal test and the analysis of variance (ANOVA) was conducted using SAS software (version 9.4) and mean comparison was conducted using the Least Significant Difference (LSD) test at α = 0.05 significance level. Principal component analysis (PCA) and pairwise correlation analysis of traits were performed using SPSS Statistics software (version 23). Results Most of the evaluated traits were affected by foliar application of nano-Ca and nano-Si treatments. Spraying with Ca and Si nano-fertilizers improved leaf area, fruit size and weight, as well as the ratio of pulp to stone in olive fruit and significantly affected the fatty acid composition in olive mesocarp. Plants treated with the combined application of 800 mg L⁻¹ nano-Ca and 60 mg L⁻¹ nano-Si exhibited maximum mean fruit weight (3.3 g) and pulp weight (2.33 g). In contrast, control plants showed significantly lower values for fruit weight (2.23 g) and pulp weight (1.38 g). Regarding fatty acid composition, nano-Ca and nano-Si treatments significantly reduced saturated fatty acid levels. The combined 800 mg L⁻¹ nano-Ca + 60 mg L⁻¹ nano-Si treatment yielded the lowest concentrations of individual saturated fatty acids: arachidic acid (0.48%), stearic acid (2.21%), and consequently the lowest total saturated fatty acid content (13.38%). The nano-Ca and nano-Si treatments significantly enhanced unsaturated fatty acid content, particularly oleic acid. Fruits treated with 800 mg L⁻¹ nano-Ca + 60 mg L⁻¹ nano-Si showed peak levels of oleic acid (75.31%) and monounsaturated fatty acids (MUFAs) (77.81%), representing increases of 21.9% and 18.9%, respectively, compared to control plants (61.80% and 65.42% for oleic acid and MUFAs, respectively). Moreover, combined application of nano-Ca and nano-Si led to a significant improvement in the qualitative characteristics of olive oil including the ratio of oleic acid to linoleic acid and MUFAs to polyunsaturated fatty acids (PUFAs) that would be of great importance from both nutritional and industrial perspectives. Specifically, the combined application of 800 mg L−1 nano-Ca and 60 mg L−1 nano-Si resulted in the maximum ratio of oleic acid to linoleic acid (10.19), unsaturated fatty acids to saturated fatty acids (6.44), and MUFAs to PUFAs (9.38). The combined foliar spraying of nano-Si and nano-Ca significantly enhanced their accumulation in both leaves and fruits of olive trees, with the highest tissue concentrations observed at the maximum application rates (800 mg L⁻¹ nano-Ca + 60 mg L⁻¹ nano-Si). Strong positive correlations was observed between oleic acid content and Ca concentrations in both fruit (r = 0.94; p ≤ 0.01) and leaf (r = 0.96; p ≤ 0.01). Additionally, MUFAs content exhibited significant association with Si levels in olive fruits and leaves (r = 0.67; p ≤ 0.05), as well as with Ca content in fruits (r = 0.92; p ≤ 0.01) and leaves (r = 0.95; p ≤ 0.01). Conclusion The findings of this study emphasized the advantage of foliar spraying with Si and Ca nanoparticles on olive tree. Moreover, this study highlight the synergistic effects between silicon and calcium, as the simultaneous application of these two elements had more beneficial impacts on the olive fruit than their individual utilization.